“The Machines Don’t Lie”: A Study of the Social Production of Mechanization in the Determination of Voter Intent - Chapman, Debra D.; Eglin, Peter (Qualitative Sociology Review, 2014)
Because election results are the essential measure of the popular will in liberal democracies, accurate determination of voter intent is a necessary pre-requisite since “what [N] does is not simply make a mark on a piece of paper; he [sic] is casting a vote” (Peter Winch). If every vote counts, then every valid vote must be counted – which means seeing the mark on the paper as intentional action. But, electronic voting systems are increasingly used in Canada. Given the operational vagaries of the use of such machines, the paper asks: How is voter intent mechanically achieved as a practical, social accomplishment of the human beings charged with working the machines and counting the votes?The paper then reports a case study of the tallying of ballots in one municipality in a recent Ontario municipal election where the official result between the two top candidates was a difference of one vote. It focuses on the social production of mechanical consistency in the determination of voter intent during the recount process.